A Study of Intramolecular Hydrogen Bonding in Levoglucosan Derivatives - Quiquempoix, Lucas (Molecules, 2017)
Organofluorine is a weak hydrogen-bond (HB) acceptor. Bernet et al. have demonstrated its capability to perturb OH···O intramolecular hydrogen bonds (IMHBs), using conformationally rigid carbohydrate scaffolds including levoglucosan derivatives. These investigations are supplemented here by experimental and theoretical studies involving six new levoglucosan derivatives, and complement the findings of Bernet et al. However, it is shown that conformational analysis is instrumental in interpreting the experimental data, due to the occurrence of non-intramolecular hydrogen-bonded populations which, although minor, cannot be neglected and appears surprisingly significant. The DFT conformational analysis, together with the computation of NMR parameters (coupling constants and chemical shifts) and wavefunction analyses (AIM, NBO), provides a full picture. Thus, for all compounds, the most stabilized structures show the OH groups in a conformation allowing IMHB with O5 and O6, when possible. Furthermore, the combined approach points out the occurrence of various IMHBs and the effect of the chemical modulations on their features. Thus, two-center or three-center IMHB interactions are observed in these compounds, depending on the presence or absence of additional HB acceptors, such as methoxy or fluorine.